“Where the Mysterious and the Undefined Breathes and Lives”: Kathleen Winter’s Annabel as Intersex Text - Chafe, Paul (Studies in Canadian Literature / Études en littérature canadienne, 2014)
Kathleen Winter’s Annabel (2010) tells the story of Wayne Blake, a hermaphrodite born in the village of Croydon Harbour on the southeast Labrador coast. In this land of extremes, Wayne’s body defies classification, and its multiplicity not only signifies “the emptiness of signs” but also unhinges the narratives of the people and the land that come into contact with him. His intersex body defies the social norms of his parents’ societies, the linguistic parameters of self-identification, and the supposed laws of nature by which so many of these characters live their lives. Yet as the novel progresses, almost everyone and everything in this landscape come to share Wayne’s multiplicity. As a result, this article argues, Annabel is an intersex text in which everything is revealed to be more than one thing at any given time, a philosophy of people and places also found in the ecocriticism of Glen A. Love and Lawrence Buell.